CONTRARIAN STRATEGY: EVIDENCE OF PRICE REVERSAL ON WINNER-LOSER PORTFOLIOS - Kusmayadi, Iwan; Suprayetno, Djoko; Wardani, Laila; Abidin, Zainal; Ahyar, Muhammad; Sri Oktaryani, G. A. (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study aims to analyze the effectiveness of the contrarian strategy by demonstrating the existence of price reversal phenomena in winner-loser stock portfolios on the Indonesia Stock Exchange (IDX). This research differs from previous studies by comprehensively exploring the Indonesian stock market (IDX), which has characteristics distinct from developed countries. Thus, this research contributes new insights to the investment literature in emerging markets. The research approach is quantitative, utilizing monthly data in the form of stock closing prices from all companies listed on the IDX from January 2020 to June 2023, totaling 866 companies, with a selected sample of 670 companies. The hypothesis was tested using an independent sample t-test. The results show that the winner and loser stock portfolios experienced price reversal in the first month after the formation period. However, in the second and third months, the winner stock portfolio did not experience a price reversal but showed significant changes. Meanwhile, the loser stock portfolio experienced price reversals in the first, second, and third months after the formation period. Both portfolios exhibit significant differences in AAR and CAAR values, leading to the general conclusion that price reversal symmetry occurred. Such conditions present opportunities for investors or traders, serving as signals to make contrarian decisions buying loser stocks or selling winner stocks. This phenomenon also provides evidence of the winner-loser anomaly in the Indonesian capital market.